Familiarity Does Not Breed Contempt: Generosity, Discrimination, and Diversity in Delhi Schools - Rao, Gautam (The American economic review, 2019)
I exploit a natural experiment in Indian schools to study how being integrated with poor students affects the social behaviors and academic outcomes of rich students. Using administrative data, lab and field experiments to measure outcomes, I find that having poor classmates makes rich students (i) more prosocial, generous, and egalitarian; and (ii) less likely to discriminate against poor students, and more willing to socialize with them. These effects are driven by personal interactions between rich and poor students. In contrast, I find mixed but overall modest impacts on rich students’ academic achievement.